PENGARUH PENEMPATAN TENAGA KERJA DAN KOORDINASI KERJA TERHADAP MOTIVASI KERJA PEGAWAI PADA PT. AKADEMI MANDIRI MEDAN - HAFIDZA RAHMANA; MELVA SITANGGANG; KARINA SILAEN (LP2MTBM MAKARIOZ, 2019)
The purpose of this study was to determine (1) the effect of workforce placement on employee work motivation (2) the effect of work coordination on employee work motivation (3) the effect of workforce placement and work coordination on work motivation simultaneously or together. This type of research is an associative research with a descriptive approach. The population in this study were all employees of PT Akademi Mandiri Medan, amounting to 57 people. The sample size taken in this study were all 57 employees who were determined using saturated sampling techniques. The variables of this study are work placement (X1), work coordination (X2) and employee motivation (Y). The results of the study show that (1) work placement has a positive influence on employee work motivation at PT Akademi Mandiri Medan (2) work coordination as well there is a positive effect on employee work motivation (3) Workforce placement and work coordination together have a positive effect on employee work motivation at PT Akademi Mandiri Medan.